2005
DOI: 10.1115/1.1812778
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Flow and Thermal Development of a Row of Cooling Jets Impinging on a Rotating Concave Surface

Abstract: The paper reports an experimental study of impingement cooling in a rotating passage of semi-cylindrical cross section. Cooling fluid is injected from a row of five jet holes along the centerline of the flat surface of the passage and strikes the concave surface. The cooling passage rotates orthogonally about an axis parallel to that of the jets. Tests have been carried out, using water, both within the passage and as the jet fluid, at a fixed Reynolds number of 15,000, for clockwise and counter-clockwise rota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(15 citation statements)
references
References 6 publications
3
12
0
Order By: Relevance
“…In order to derive this correlation a functional relationship of the form Nu ¼ CRe m ðD=BÞ n ðh=BÞ p (10) is assumed where, the constant C and the exponents m, n, and p are to be determined through a regression analysis of the 64 predicted data points for the different cases consisting of combinations of the above parameters. The desired functional relationship is obtained as Nu ¼ 0:107Re 0:761 ðD=BÞ À0:346 ðh=BÞ À0:047 (11) The separation parameter (h/B) has a rather weak effect on the average Nusselt number since its exponent is much smaller compared to that of the other parameters. Also the average Nusselt number varies inversely with the surface curvature and spacing (negative exponent) and directly with the Reynolds number (positive exponent).…”
Section: Results Of the Parametric Study And Discussionmentioning
confidence: 99%
“…In order to derive this correlation a functional relationship of the form Nu ¼ CRe m ðD=BÞ n ðh=BÞ p (10) is assumed where, the constant C and the exponents m, n, and p are to be determined through a regression analysis of the 64 predicted data points for the different cases consisting of combinations of the above parameters. The desired functional relationship is obtained as Nu ¼ 0:107Re 0:761 ðD=BÞ À0:346 ðh=BÞ À0:047 (11) The separation parameter (h/B) has a rather weak effect on the average Nusselt number since its exponent is much smaller compared to that of the other parameters. Also the average Nusselt number varies inversely with the surface curvature and spacing (negative exponent) and directly with the Reynolds number (positive exponent).…”
Section: Results Of the Parametric Study And Discussionmentioning
confidence: 99%
“…However, due to the interaction of the centrifugal, buoyancy, and Coriolis force in the rotation condition, the flow became very complex. Iacovides et al [15,16] studied the flow and thermal characteristics of a row of cooling jets impinging on a rotating concave surface. The local Nusselt number was measured using the thermochromic liquid crystal (TLC) technique.…”
Section: Introductionmentioning
confidence: 99%
“…Mattern et al [7] reported the local heat/mass transfer distributions on the curved impinging plate with regard to various parameters such as hole-to-hole spacing, hole-to-plate spacing, and jet orientation. Iacovides et al [8] researched the impinging jet under the ultimate rotation condition with Ro = 0.18 and suggested the Nusselt number on the impinging surface. They reported that all secondary peaks and some of the primary peaks in array jets disappear due to strong rotation effect.…”
Section: Introductionmentioning
confidence: 99%